Strategi Manajerial Kepala Madrasah dalam Penguatan Disiplin Kerja Guru di Madrasah Tsanawiyah Negeri 1 Batang Hari - Putri Wulandari; Mahmud MY; Ajuzar Fiqhi (JMiE (Journal of Management in Education), 2025)
This study aims to analyze the managerial strategies of the madrasah principal in strengthening teachers’ work discipline at Madrasah Tsanawiyah Negeri 1 Batang Hari. The research employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students as research subjects. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the madrasah principal implements integrated managerial strategies through the functions of planning, organizing, actuating, and controlling. These strategies are manifested in the formulation of clear disciplinary policies, proportional task distribution, leadership by example, continuous coaching, and consistent disciplinary evaluation. The implementation of these managerial strategies has a positive impact on improving teachers’ work discipline, fostering a conducive learning environment, and strengthening the organizational culture of the madrasah. This study contributes theoretically and practically to the development of human resource management in the context of Islamic education.